You need grouping symbols for your logical expression.
$(A \wedge \neg B \wedge \neg C) \vee (\neg A \wedge B \wedge \neg C) = [(A\wedge \neg B)\vee (\neg A\wedge B)]\wedge C $
Note the brackets. What you wrote could be interpreted two different ways.
Anyway, the last column is wrong
You did or rather than and.
Here is the last column: SEE HERE
BTW: It should be $(A \wedge \neg B \wedge \neg C) \vee (\neg A \wedge B \wedge \neg C) = [(A\wedge \neg B)\vee (\neg A\wedge B)]\wedge \neg C$
Thanks Plato ,
I'm off to bed now as my math brain is full and I have these lectures early tomorrow ,
Thanks once again I'll understand it alot better when the lecturer speaks
really much appreciated
cheers